Unusual Benefit of Lumbar Sympathetic Block in Filarial Lymphedema - Kritika Doshi (Indian Journal of Pain, 2025)
Lymphatic filariasis, commonly known as elephantiasis, is a neglected tropical disease which causes hidden damage to the lymphatic system resulting in disfigurement, suffering, and poor quality of life. Lumbar sympathetic block is routinely used by pain physicians for vascular insufficiency, sympathetically mediated pain, hyperhidrosis, and discogenic pain as usual indications. There is no report in literature of performing a sympathetic block for filarial lymphedema. The author would like to report this case of a patient of filarial lymphedema and pain who benefitted with a lumbar sympathetic block.